Sub-national stratification of malaria risk in mainland Tanzania: a simplified assembly of survey and routine data - Thawer, SG; Chacky, F; Runge, M; Reaves, E; Mandike, R; Lazaro, S; Mkude, S; Rumisha, SF; Kumalija, C; Lengeler, C; Mohamed, A; Pothin, E; et al. (BioMed Central, 2020)
Background Recent malaria control efforts in mainland Tanzania have led to progressive changes in the prevalence of malaria infection in children, from 18.1% (2008) to 7.3% (2017). As the landscape of malaria transmission changes, a sub-national stratification becomes crucial for optimized cost-effective implementation of interventions. This paper describes the processes, data and outputs of the approach used to produce a simplified, pragmatic malaria risk stratification of 184 councils in mainland Tanzania.